Victorians undone : tales of the flesh in the age of decorum - Hughes, Kathryn, 1959- (Johns Hopkins University Press, 2018)
"A groundbreaking account of what it was like to live in a Victorian body from one of our best historians ... brings the Victorians back to life and helps us understand how they lived their lives"--Publisher's description.